2009
DOI: 10.1111/j.1468-232x.2009.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Employers’ Online Search: An Empirical Analysis

Abstract: Drawing on job postings at an online job board, we find that employers who have to fill their vacancies immediately specify fewer job requirements, provide more details about the job application process, and are quicker to withdraw their vacancies from the job board than employers with job openings that do not have to be filled immediately. These findings offer new insights into the role of vacancy costs in determining how employers search for workers online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The information systems (ISs) used by each respondent and the respective departments of the respondents were the two dimensions of TECs (Goodhue and Thompson, 1995). The main technical features leading to useful EWs that have been proposed by different researchers include the number of vacancies, matching productivity, search ability, resume production, and resume remanufacturing (Brenčič, 2014;Brenčič & Norris, 2009;Jansen, Jansen, & Spink, 2005;Selden & Orenstein, 2011). Therefore, the hypotheses are as follows:…”
Section: Ttfmentioning
confidence: 99%
“…The information systems (ISs) used by each respondent and the respective departments of the respondents were the two dimensions of TECs (Goodhue and Thompson, 1995). The main technical features leading to useful EWs that have been proposed by different researchers include the number of vacancies, matching productivity, search ability, resume production, and resume remanufacturing (Brenčič, 2014;Brenčič & Norris, 2009;Jansen, Jansen, & Spink, 2005;Selden & Orenstein, 2011). Therefore, the hypotheses are as follows:…”
Section: Ttfmentioning
confidence: 99%
“…Internet facilitates the acquisition of information from applicants, and the provision of tailored information about the organization allows rapid and frequent changes in the job description to improve the search outcomes, plays an active role in targeting promising applicants, and even helps organizations to project an image of being innovative that ultimately influence application and acceptance intentions (Autor, 2001;Cappelli & Wilk, 2003;Galanaki, 2002;Chapman & Webster, 2003;Nakamura et al, 2009;Brencic & Norris 2009;Brencic & Norris 2012).…”
Section: Social Networking Sites and Effective Recruitmentmentioning
confidence: 99%
“…Brencic and Norris (, ) are among the few researchers to have studied online employer search, and they found that most employers do not modify salary offerings or job requirements in the advertisements they post on online job boards. Employers who need to fill their vacancies immediately tend to specify fewer job requirements, provide more information about the job and remove vacancies more quickly from the job boards.…”
Section: Recruitment Channels and Employer Searchmentioning
confidence: 99%
“…Another under‐researched area is the role of the Internet in recruiting. Among the few studies on online employer search, Brencic and Norris (, ) found that employers who have to fill vacancies immediately specify fewer job requirements, provide more information about the job and are quicker to remove vacancy announcements from recruitment websites. Additionally, most employers do not modify the salary or job requirements posted in their online advertisements despite the high costs of continuing their search.…”
Section: Introductionmentioning
confidence: 99%